Use of verbal autopsy to determine mortality patterns in an urban slum in Kolkata, India - Suman Kanungo; Ataru Tsuzuki; Jacqueline L Deen; Anna Lena Lopez; Krisnan Rajendran; Byomkesh Manna; Dipika Sur; Deok Ryun Kim; Vinay Kumar Gupta; R Leon Ochiai; Mohammad Ali; Lorenz von Seidlein; et al. (The World Health Organization, 2010)
OBJECTIVE: To define mortality patterns in an urban slum in Kolkata, India, in the context of a cholera and typhoid fever project. METHODS: In a well-defined population that was under surveillance for 18 months, we followed a dynamic cohort of 63788 residents whose households were visited monthly by community health workers to identify deaths. Trained physicians performed verbal autopsies and experienced senior physicians assigned the primary cause of death according to the International classification of diseases, 10th edition. We tabulated causes of death in accordance with Global Burden of Disease 2000 categories and assessed overall and cause-specific mortality rates per age group and gender. FINDINGS: During 87921 person-years of follow-up, we recorded 544 deaths. This gave an overall mortality rate of 6.2 per 1000 person-years. We assigned a cause to 89% (482/544) of the deaths. The leading causes of death, in descending order, were cardiovascular diseases (especially among adults aged over 40 years), cancer, respiratory ailments and digestive disorders. Most deaths in children under 5 years of age were caused by tuberculosis, respiratory infections and diarrhoeal diseases. CONCLUSION: Although the most common causes of death in children were infectious, non-communicable diseases were predominant among adults. There is a need for continuing interventions against infectious diseases in addition to new and innovative strategies to combat non-infectious conditions.